Foreign direct investment and export competitiveness in Africa: Investigating the channels - Gladys Gamariel; Seedwell Hove (Journal of African Trade, 2019)
Foreign Direct Investment (FDI) into Africa has surged in recent years. At the same time, international trade has increased, exposing African countries to international competition. This raises the question of whether FDI plays a role in enhancing export competitiveness. This study investigates the impact of FDI on export competitiveness in countries in Sub-Saharan Africa, focusing on the channels of influence. It uses the system generalized method of moments technique, and considers an index of export sophistication as a measure of competitiveness. The study shows that FDI stimulates export competitiveness. Several other factors also enhance export competitiveness, such as human capital, export demand, macroeconomic environment, and the quality of institutions. However, unit labor costs and reduced foreign market access lower export competitiveness. The key channels through which FDI affects export competitiveness are human capital, technological spillovers in the form of forward linkages, and enhancement of domestic productivity. The study also confirmed the possible competition and domination effects of FDI on export competitiveness, which works to crowd out local producers by foreign firms. The results are robust to sensitivity tests including alternative estimation methods and alternative measures of competitiveness. Policy reforms should focus on building human capital and strengthening economic linkages in order to catalyze technological transfers and enhance productivity and competitiveness.
Keywords: F14; F21; 330; Export competitiveness; export sophistication; Foreign direct investment; channels